COMMUNITY-BASED SURVEILLANCE (CBS) OF ACUTE FLACCID PARALYSIS CASES, IN SECURITY CHALLENGED SETTINGS IN FAR NORTH REGION OF CAMEROON - N. Nkem; A.M.-E. Tchalla Abalo; K. Mugenyi; J. Magoola; A. Asanji; D. Ekosso; C. Ngouateu; J.P. Six Moke; C.D. Apollo; H. Samba; A.H. Aboubacar; S. Abdoulaye Seid; et al. (International Journal of Infectious Diseases, 2023)
Intro: As a nouveau approach for active surveillance of Acute Flaccid Paralysis (AFP) in Cameroon, community-based surveillance (CBS) of AFP has been implemented in security challenged settings in Far North Region of Cameroon since 2015. This article displays the contribution of CBS to AFP surveillance over the years in the areas of intervention. Methods: This transverse study analyzed the performance of CBS of AFP from 2015 to June 2022 in 10 conflict hit health districts in the Far North region of Cameroon. The 10 health districts were enrolled progressively from 2015-2022. A data capture sheet was used to extract data from the national database, cleaned and analyzed using excel_365. The indicators measured included AFP case notification, stool adequacy and annualized non-polio AFP (ANPAFP) rate. Findings: Over 458 AFP cases were notified between 2015-June 2022, with 234 (51%) by CHW and 224 (49%) by health personnel compared to 252 cases notified between 2003-2014 by health personnel. The proportion of cases notified by CHWs increased from 15% in 2015 to over 80% in 2022. The mean age of notified cases was 4.1±3.9. Stool adequacy rate was 87.7% (87.4% Female and 86.1% Male) throughout the period. The ANPAFP rate per 100,000 under-15 children improved from averagely 2.4 per 100000 between 2003-2014 to over 11.6 per 100000 between 2015-2022. During the period of analysis, the last wild poliovirus was seen between 2013-2014 (health personnel), however, four circulating Vaccine Derived Poliovirus Type 2 (cVDPV2) cases were detected in 2021 by CHWs in the zones of intervention. Conclusion: The results above show the enormous contribution of CBS of AFP over the years with a great improvement of the measured indictors over time. Close supervision and monitoring of activities of community health workers in AFP surveillance improved detection and notification of cases over the years.